“To Follow the Law and Conscience”: Hard Skills and Soft Skills in the Legal Education - Ekaterina A. Koval (National Research Mordova State University, 2020)
Introduction. The study is devoted to investigation of methods to integrate “hard” and “soft” skills of law students. This approach is necessary for teaching students to make decisions in situations of value and norm uncertainty, which require the integration of law and morality, general cultural and professional competencies. The public use of hate speech is chosen as an example of a value-ambiguous problem. This problem involves the search for a certain balance of public and private interests, the right to freedom of expression and protection against discrimination, insult, stigmatization, the right to respect for private and family life. Materials and Methods. 62 students of legal specialities and areas of training were involved in the case study. Case materials were structured according to the levels of educational goals in accordance with Bloom’s classic taxonomy. The case is devoted to the analysis of the controversial commentary of Savva Terentyev. Results. The use of the case-method for decision-making under conditions of value-normative uncertainty (using the example of counteracting hate speech) made it possible to integrate the general cultural and professional competencies of law students, to involve students, who do not usually participate in discussions, in active group work. However, there are limitations to the use of the case method for integrating “hard” and “soft” skills: preparation for the lesson is resource-intensive for both teacher and students; case materials quickly become obsolete and require constant updating and processing; the choice of material and its presentation in the classroom require a special pedagogical tact and a clear arrangement of axiological accents. Discussion and Conclusion. The results can be used to develop educational cases where general cultural and professional competencies of law students can be integrated, as well as to teach students how to make decisions in the face of value and norm uncertainty and to carry out personal and professional development.